The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1108/mbe-10-2022-0126
|View full text |Cite
|
Sign up to set email alerts
|

Mediating effect of entrepreneurial passion in the relationship between entrepreneurial orientation and innovative work behavior

Abstract: Purpose This paper aims to analyze the mediating effect of entrepreneurial passion on the relationship between entrepreneurial orientation and innovative work behavior in employees of small- and medium-sized enterprises (SMEs) in Peru. Design/methodology/approach A nonexperimental cross-sectional design was used. Data were obtained from a random sample of 300 employees of SMEs in the manufacturing, agricultural and livestock sectors in Peru. Findings The results showed that entrepreneurial orientation has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 70 publications
(164 reference statements)
1
3
0
Order By: Relevance
“…In line with prior research, the study confirmed that motivation and concern for social welfare significantly predict EO. This finding is consistent with research suggesting that individuals who are motivated to start businesses and who are concerned with the social impact of their businesses are more likely to be successful entrepreneurs (Flores P erez and Guevara, 2023;To et al, 2020). Consequently, motivation and concern for social impact play important roles in promoting entrepreneurial activity.…”
Section: Motivational Factors Of Entrepreneurial Orientationsupporting
confidence: 89%
See 2 more Smart Citations
“…In line with prior research, the study confirmed that motivation and concern for social welfare significantly predict EO. This finding is consistent with research suggesting that individuals who are motivated to start businesses and who are concerned with the social impact of their businesses are more likely to be successful entrepreneurs (Flores P erez and Guevara, 2023;To et al, 2020). Consequently, motivation and concern for social impact play important roles in promoting entrepreneurial activity.…”
Section: Motivational Factors Of Entrepreneurial Orientationsupporting
confidence: 89%
“…Accordingly, the concept of work is being referred to as an opportunity to achieve their ultimate interests. These two also correlate to the idea of supplementing household income, which is another motivational force (Autin et al, 2019;Flores P erez and Guevara, 2023). McClelland's theory emphasizes the significance of an individual's internal motives, specifically the need for achievement, in driving EO, and the identified variables in this review align with this theory.…”
Section: Motivational Factors and Entrepreneurial Orientationmentioning
confidence: 91%
See 1 more Smart Citation
“…The perspective of harmonious passion-a component of work passion that is driven by a person's free will and compatible with other aspects of life-is adopted by the study. Positive engagement is encouraged by harmonious passion both while and after participating in connected activities (Flores Peŕez & Guevara, 2023;Santos & Cardon, 2019).…”
Section: Entrepreneurship Passion and Digital Innovation In Family Bu...mentioning
confidence: 99%